2018
DOI: 10.1002/ece3.3976
|View full text |Cite
|
Sign up to set email alerts
|

Brain gene expression analyses in virgin and mated queens of fire ants reveal mating‐independent and socially regulated changes

Abstract: Transcriptomes of dissected brains from virgin alate and dealate mated queens from polygyne fire ants (Solenopsis invicta) were analyzed and compared. Thirteen genes were upregulated in mated queen brain, and nine were downregulated. While many of the regulated genes were either uncharacterized or noncoding RNAs, those annotated genes included two hexamerin proteins, astakine neuropeptide, serine proteases, and serine protease inhibitors. We found that for select differentially expressed genes in the brain, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 74 publications
(124 reference statements)
1
25
0
Order By: Relevance
“…Together, our results dovetail with those from eusocial insects [honey bees and ants: (7174)], sticklebacks and cichlid fish (18, 60, 75, 76), and rodents (61, 77, 78) to emphasize the importance of social modulation of gene regulation, including both gene expression levels and epigenetic states. Our findings specifically reinforce the role of social interactions in immune cell gene regulation, building substantially on our prior work (9, 10) by revealing a key role for chromatin dynamics and accessibility to TF binding.…”
Section: Discussionsupporting
confidence: 81%
“…Together, our results dovetail with those from eusocial insects [honey bees and ants: (7174)], sticklebacks and cichlid fish (18, 60, 75, 76), and rodents (61, 77, 78) to emphasize the importance of social modulation of gene regulation, including both gene expression levels and epigenetic states. Our findings specifically reinforce the role of social interactions in immune cell gene regulation, building substantially on our prior work (9, 10) by revealing a key role for chromatin dynamics and accessibility to TF binding.…”
Section: Discussionsupporting
confidence: 81%
“…By targeting the most relevant sensory organ associated with this behavior, our study provided better sensitivity to detect tissue-specific differences compared to similar studies which used the whole bodies of workers (Wang et al, 2008) and queens (Nipitwattanaphon, Wang, Dijkstra, & Keller, 2013). Other transcriptomics experiments have been conducted in fire ants in other contexts (Calkins et al, 2018;Chen, Shen, & Lee, 2006;Morandin et al, 2016;Nipitwattanaphon et al, 2014;Qiu et al, 2018). Our results and follow-up experiments uncovered an interesting, differentially expressed OBP, SiOB12b′, whose expression patterns suggest that it may play a role in the differences between monogyne and polygyne colony forms in fire ants.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in contrast to worker bees, none of the four Vg genes were regulated in workers by topical application of the JH-analog S-hydroprene [10]. In a different study, we have shown that when comparing brain transcriptomes of alate virgin and dealate mated queens, the expression of two hexamerins, hexamerin-like (LOC105192919, hereafter called hexamerin 1 ) and arylphorin subunit alpha-like (LOC105192898), is significantly reduced in brains of mated queens [41]. In the same transcriptome analysis, no differences in expression were observed for the other two hexamerin genes, hexamerin (LOC105204474, hereafter called hexamerin 2 ) and arylphorin subunit beta (LOC105192897).…”
Section: Introductionmentioning
confidence: 99%